Strategy Innovation of Hajj Savings Product: an Effort to Maintain Customer Loyalty at BMT Fauzan Aziima Parepare - Sukawati, Anita; Trimulato, Trimulato; Lismawati, Lismawati; Nuringsih, Nuringsih (Fakultas Syariah IAIN Kerinci, 2023)
The purpose of this research is to describe the product innovation strategy for Hajj savings at BMT Fauzan Aziima and efforts to maintain customer loyalty. The type of research used is a field study conducted directly at BMT Fauzan Aziima, Parepare city. This research is a qualitative research that describes the research results from the data obtained. The data source used is primary data obtained directly and supplemented with secondary data that supports the research. Data collection techniques used were interviews with institutions and interviews with customers, as well as data from the literature. The data analysis technique used in this study is descriptive qualitative, which describes the strategies undertaken by BMT Fauzan Aziima in innovating hajj savings products and efforts to maintain customer loyalty. The results of this study show BMT Fauzan Azhiima's product innovation, namely the Hajj Savings Product. BMT Fauzan Azhiima didn't just sit there. BMT Fauzan Azhiima uses a strategy, namely by visiting prospective customers directly, such as going directly to the field to promote products to each prospective customer. Increased loyalty of hajj customers at BMT Fauzan Azhiima Parepare City This can be proven by the increase in customers from 2015 to 2017 of 18.06%. By innovating products will increase public interest in saving at BMT. Product innovation as an effort to attract more customers and become a differentiator from conventional products.